(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
The absence of active student participation in learning activities is one of the many difficulties teachers encounter, particularly in Islamic Religious Education (PAI) subjects. This condition is generally caused by the use of learning models that are less innovative and less interesting, so that the level of student participation is low. The purpose of this study is to describe how the Teams Games Tournament (TGT) learning model is being used at SMP Negeri 5 Bukittinggi to increase student engagement in PAI courses and to identify the elements that facilitate and hinder its use. The study employs a case study methodology and qualitative approaches. Ten pupils in class VIII.3 of SMP Negeri 5 Bukittinggi, the curriculum deputy principal, and PAI teachers provided the data. While data analysis is done through the steps of data reduction, data presentation, and conclusion drawing, data collection methods include documentation, observation, and interviews. Technical triangulation and source triangulation were used to assess the data’s veracity. According to the research findings, using the TGT model has a beneficial effect on raising student engagement in PAI courses. Implementing the Independent Curriculum in schools, teachers’ inventiveness, the availability of suitable resources and infrastructure, and effective teamwork are all elements that contribute to successful implementation. The inhibiting factors include limited learning time, differences in student abilities, and unsupportive classroom conditions.